ANALISIS HUBUNGAN TEKANAN PANAS, KARAKTERISTIK PEKERJA DAN PEKERJAAN TERHADAP KELELAHAN PADA PEKERJA KONSTRUKSI JALAN TOL KM 1,7 – KM 7,25 JOGJA BAWEN - Auliauliman Putera, Irza; Sembiring, Edison Cholia; Sekwika, Tatan (Universitas Bina Taruna Gorontalo, 2025)
This study aims to analyze the relationship between heat stress, worker characteristics, and work conditions with fatigue in toll road construction workers. Using a cross-sectional quantitative approach, data were collected from 100 workers through observation, interviews, and questionnaires. Data analysis using Spearman Rho showed that heat stress, worker characteristics such as age and experience, and job aspects such as duration and intensity, were significantly correlated with work fatigue. These results revealed that hot work environment conditions, worker demographics, and workload had a significant effect on fatigue levels. Based on these findings, interventions are proposed to reduce work fatigue, including educational programs on fatigue management, provision of rest facilities, reduction of dust and temperature in the work area, and provision of sanitation facilities. These interventions are expected to improve worker welfare and reduce fatigue in the construction environment.